Swipe at first sight: The Continuous Intention to use Dating Apps in Malaysia - Kishen Balan Balan; Fitriya Abdul Rahim; Zufara Arneeda Zulfakar; Goh Poh Jin; Mahendra Kumar Chelliah (Universitas Internasional Batam, 2021)
Dating apps aim to help you meet someone. Many found success in finding love online encouraging dating apps developers to further ingrained themselves into the modern-day matchmaking culture. This study recommends a research model examining the antecedents of users’ intention to continuously use dating apps. It focuses on the influence of gratifications from the use of dating apps towards perceived usefulness and continuance intention as well as the role of perceived usefulness as a mediator. The result shows a positive relationship between gratifications and continuance intention. Although not strong, the perceived usefulness does acts as a mediator in this relationship